Economic evaluation of border closure for a generic severe pandemic threat using New Zealand Treasury methods. (8th August 2018) - Boyd, Matt; Mansoor, Osman D.; Baker, Michael G.; Wilson, Nick
Abstract: Objective: To perform a comprehensive economic evaluation of border closure for an island nation in the face of severe pandemic scenarios. Methods: The costing tool developed by the New Zealand (NZ) Treasury (CBAx) was used for the analyses. Pandemic scenarios were as per previous work; 1 epidemiological data were from past New Zealand influenza pandemics. Results: The net present value of successful border closure was NZ$7.86 billion for Scenario A (half the mortality rate of the 1918 influenza pandemic) and $144 billion for preventing a more severe pandemic (10 times the mortality of scenario A). Cost–utility analyses found border closure was relatively cost‐effective, at $14, 400 per QALY gained in Scenario A, and cost‐saving for Scenario B (taking the societal perspective). Conclusions: This work quantifies the economic benefits and costs from border closure for New Zealand under specific assumptions in a generic but severe pandemic threat (e.g. influenza, synthetic bioweapon). Preparing for such a pandemic response seems wise for an island nation, although successful border closure may only be feasible if planned well ahead. Implications for public health: Policy makers responsible for generic pandemic planning should explore how border closure could be implemented, including practical and legal frameworks.